2016
DOI: 10.7314/apjcp.2016.17.1.311
|View full text |Cite
|
Sign up to set email alerts
|

Nurses, Healthy Women and Preventive Gynecological Examinations - Vlora City Scenario, Albania

Abstract: Background: Nurses play an important role in preventive medicine because they represent the largest sector of health professionals. This role is very crucial in developing countries, which are going through rapid societal and economic changes, associated with a rising burden of cancers due to different risk factors. The current study aimed to compare health awareness between nurses and healthy women regarding preventive gynecological examinations and to answer the question -can nurses make a difference in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Despite these findings, poor knowledge of cervical cancer has also been reported from other similar studies conducted in other countries [16][17][18]. Comparably, our findings are consistent with other Albanian studies focused on other groups of female students, reporting insufficient knowledge about cervical cancer, disease risk factors, and screening methods [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…Despite these findings, poor knowledge of cervical cancer has also been reported from other similar studies conducted in other countries [16][17][18]. Comparably, our findings are consistent with other Albanian studies focused on other groups of female students, reporting insufficient knowledge about cervical cancer, disease risk factors, and screening methods [20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, there are some studies that provide an overview of cervical cancer knowledge and behaviours screening among healthy female, but the authors have dedicated their work more often to a local population, for example Vlora's healthy women or female healthcare practitioners. According to Kamberi et al (2016), Kamberi, Theodosi, Bilushi, Cuberi, and Sinaj (2014), Kamberi, Theodosi, Ndreu, Sinaj, and Kamberi (2015), found poor knowledge of symptoms and risk factors for cervical cancer among women in general and female Healthcare Practitioners (HCPs) in particular. Large numbers of women never screened.…”
Section: Resultsmentioning
confidence: 99%
“…If he feels that the test will benefit their patients, the likelihood of performing the test increases. Some systemic review found a positive correlation of educational level, financial status, and an awareness of the mortality rates associated gynecological cancer with gynecological cancer attendance [26,31,32]. The level of knowledge and attitude toward health check-up are related to multiple factors such as ethnicity, place of residence, income, and social-economic status [33][34][35][36][37].…”
Section: Gynecological Cancer Screening Intervalsmentioning
confidence: 99%